Literature analysis challenges to sustainalbe development in the Mekong Delta : (The Sustainable Mekong Research Network (Sumernet), 2007)
This report brings together an analysis of how livelihoods, economic development and natural resources management in the delta have been influenced by national policy changed, integration into the international market economy and concomitant regional process to understand the current state of knowledge on key challenges for sustainable development.